Investigations of the Theileria parva carrier-state in cattle at the livestock/wildlife interface of the uPhongolo-Mkuze area in KwaZulu Natal, South Africa - Latif, Abdalla A. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.